Upaya Peningkatan Produktivitas Kinerja Karyawan Pada UMKM Keripik Lampung Ibu Satih Desa Baturaja Kecamatan Way Lima Kabupaten Pesawaran - Zatika, Dinda Ana; A.K Yohanson; Yuniwati (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
MSMEs are one of the important pillars in regional economic development, but many still face problems in terms of employee management and work productivity. This community service activity aims to improve the productivity of employee performance of Ibu Satih's Lampung Chips MSME through training, mentoring, and implementation of a more structured work system. The implementation method includes observation, interviews, time management training, preparation of standard operating procedures (SOPs), and evaluation of work results. The results of the activity showed a significant increase in production output, work time efficiency, and employee morale. The implementation of SOPs and clear division of tasks encourage the creation of a more disciplined and productive work culture. In addition, this activity builds awareness of owners and employees about the importance of teamwork and the role of management in increasing business competitiveness. This community service activity is expected to be a model for improving employee performance for other MSMEs with similar characteristics.